The Influence of Internal Auditors' Objectivity and Professionalism on the Quality of Audit Results (Empirical Study at the Bandung Regency Regional Inspectorate) - Irawan, Ferdy; Romli, Romli (Dinasti Publisher, 2026)
This study aims to analyze the influence of objectivity and professionalism of internal auditors on the quality of audit results at the Bandung Regency Regional Inspectorate, both partially and simultaneously. The background of the study is based on the phenomenon of suboptimal recommendations from government agency accountability performance evaluations and findings of weaknesses in fixed asset management. The research method used is quantitative descriptive with a saturated sample of 67 internal auditors as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 31 software. The results show that partially, objectivity behavior does not have a positive and significant effect on the quality of audit results. Meanwhile, professionalism behavior has a positive and significant effect on the quality of audit results. Simultaneously, these two variables influence the quality of audit results by 52.3%, while the remaining 47.7% is influenced by other factors outside the research variables. In conclusion, increasing impartiality and implementing strict professional standards will collectively increase the credibility of local government audit reports.